If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -9x + 13 = n Reorder the terms: 7 + 13 + -9x = n Combine like terms: 7 + 13 = 20 20 + -9x = n Solving 20 + -9x = n Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -9x = -20 + n Combine like terms: 20 + -20 = 0 0 + -9x = -20 + n -9x = -20 + n Divide each side by '-9'. x = 2.222222222 + -0.1111111111n Simplifying x = 2.222222222 + -0.1111111111n
| 4x^2-37x-119=0 | | (3x)+(2x-5)=90 | | -68=-17x | | 8+q=19 | | -7+5p=-16(p-14) | | (x)(5x-2)=115 | | -26=-12+m | | -9(2y+6)=48 | | 54/x*10/5 | | -3/4y=-2-1/2x | | 75=-15k | | (2x)+(3x)=90 | | e^3x+5=6 | | 7x?-5x?= | | -8b=-104 | | -6(3n-1)=-120 | | f(x)=-4x^7-6x+x+2 | | 2p+4p=20+3p | | -4(3+6n)=2n+40 | | (x+5)+(3x+1)=90 | | 1/16-16z^2=0 | | 19=x/5 | | 3xy+1-6=2xy+8 | | -1.645=(x-55)/4 | | -3(x-2)=-82 | | 5x+29=17 | | 6/35=15/x | | -8(1-6b)=424 | | 1.96=(x-55)/4 | | 2x-6=3r | | (x-6)(x-9)=(x+7)(x+3) | | 1/7-3i |